2007
DOI: 10.1111/j.1365-2265.2007.02936.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone (GH) treatment reduces peripheral thyroid hormone action in girls with Turner syndrome

Abstract: GH treatment reduced TR expression in PBMC and biochemical serum markers of TH action. These results suggest that GH treatment in TS patients impair peripheral TH action at tissue level and prompt a role in the reduced growth response to the therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Previously, we reported data showing that IGF‐I and GH reduced specific T3 responses in rat tissues by a down‐regulation of TR in both rat cell culture and in vivo. 9–11 In consonance, we provided evidence for a reduced peripheral TH action induced by GH treatment to Turner Syndrome (TS) girls assessed by the measurement of TR mRNA expression in peripheral blood mononuclear cells (PBMC) and serum biochemical markers of TH action at tissue level 12 . However, these results could not be extrapolated to other patients receiving GH treatment, taking into consideration the different endogenous GH secretion as well as the different GH dosage administered to patients carrying different etiopathogenic growth deficiencies 13 .…”
Section: Introductionmentioning
confidence: 81%
“…Previously, we reported data showing that IGF‐I and GH reduced specific T3 responses in rat tissues by a down‐regulation of TR in both rat cell culture and in vivo. 9–11 In consonance, we provided evidence for a reduced peripheral TH action induced by GH treatment to Turner Syndrome (TS) girls assessed by the measurement of TR mRNA expression in peripheral blood mononuclear cells (PBMC) and serum biochemical markers of TH action at tissue level 12 . However, these results could not be extrapolated to other patients receiving GH treatment, taking into consideration the different endogenous GH secretion as well as the different GH dosage administered to patients carrying different etiopathogenic growth deficiencies 13 .…”
Section: Introductionmentioning
confidence: 81%
“…Primers were designed to distinguish cDNA and genomic DNA/pseudogenes (Kreuzer et al 1999). Primers were from Sigma (Sigma-Aldrich from Buenos Aires, Argentina) and designed to amplify bands of 591, 650 and 273 bp for TR 1 , 1 mRNA and -actin mRNAs, respectively; according to the following sequence: TR 1 forward: 5Ј-TTCAGCGAGTTTACCAAG ATCATCAC-3Ј, TR 1 reverse: 5Ј-TTAGACTTCCTGAT CCTCAAAGACCTC-3Ј; TR 1 forward: 5Ј-GTGACCGT GTAGAGTAGATG-3Ј, TR 1 reverse: 5Ј-CTCCACACCA AGTCTACAGC-3Јand -actin forward: 5Ј-CGGAACCG CTCATTGCC-3Ј, -actin reverse: 5Ј-ACCCACACTGTG CCCATCTA-3Ј (Montesinos et al 2006;Susperreguy et al 2007). PCR was carried out in a 20 l Wnal vol: 1.5 mM MgCl 2 , 4 l 5£ PCR buVer, 1 U Taq-polymerase (Promega, Madison, WI, USA), 0.25 mM each dNTP (Promega, Madison, WI, USA) and 2 l RT product.…”
Section: Total Rna Extractionmentioning
confidence: 99%
“…Of four studies identified using variable pharmacological doses of GH therapy in girls with Turner’s syndrome, two demonstrated no change in thyroid parameters 62,63 one showed a decrease in free T4 within the normal range at 6 months of therapy that returned to baseline at 1 year without any alteration in T3 64 and the most recent study found a trend towards a decrease in free T4 and an increase in T3 and TSH, all within the normal range 65 . None of the subjects became clinically or biochemically hypothyroid during GH administration, suggesting that GH unmasks rather than induces CH in at risk groups with organic pituitary disease.…”
Section: Growth Hormone Effect On the Thyroid Axismentioning
confidence: 99%